2006
DOI: 10.1007/s10803-006-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Knowledge and Lexical Use in Autism

Abstract: One aspect of autistic language that has been infrequently researched is vocabulary and the conceptual knowledge underpinning individual words or word types. In this descriptive study we investigate anomalous vocabulary use in a 70,000-word corpus of conversational autistic language and examine evidence that concept formation, and hence vocabulary, is abnormal in autism. Particular attention is paid to the expression of artifact and temporal concepts which some believe may develop abnormally in autism. Little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 27 publications
4
30
0
6
Order By: Relevance
“…Repetitive language behavior has been reported in the literature (e.g. Perkins et al, 2006), but as far as we can determine there has not been a comprehensive study of questions raised by this phenomenon.…”
Section: Repetitive Language Behaviormentioning
confidence: 89%
“…Repetitive language behavior has been reported in the literature (e.g. Perkins et al, 2006), but as far as we can determine there has not been a comprehensive study of questions raised by this phenomenon.…”
Section: Repetitive Language Behaviormentioning
confidence: 89%
“…En effet, certains enfants TSA arrivent à se baser sur le regard pour coupler des formes phonologiques (la forme sonore du mot) nouvelles avec des objets, mais ils ne parviennent pas toujours à intégrer l'information sémantique (le sens du mot) au sein de leur lexique mental, c'est-à-dire à associer le mot nouvellement acquis à une signification riche et flexible, interconnectée avec celles d'autres mots [16,17]. Cette hypothèse expliquerait pourquoi on observe souvent un vocabulaire en réception anormalement bas par rapport au vocabulaire expressif chez les enfants avec TSA, ainsi que le fait que l'utilisation de mots soit généralement figée et peu productive dans l'autisme [7,18,19].…”
Section: Pragmatique Et Acquisition Lexicale Dans Les Tsaunclassified
“…The terms of psychological state (physical, emotional, of desire and cognitive) and of designation (natural and cultural entity, body parts, action, artifacts, time and space location and people's names) were counted by occurrence. According to the studies by Lee & Rescorla (2002) and Perkins et al (2006), the number of different psychological state terms was also counted, besides its total occurrence. The results have shown that, of the total assessed variables the ones with larger number of correlations were: MLU-words, verbs, GM1, MLU morphemes and proportion of interpersonal communicative acts.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Negative associations with the gestural mean may indicate one of two things: either the use of gestures is replaced by verbalization or the use of verbal utterances doesn't exclude the gestural delay that is observed even in children with better linguistic abilities. Perkins et al (2006) stated that even before the first year of life autistic children present delayed gestural communication that is a better diagnostic factor than word production or comprehension.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation